Enhanced Hepatocarcinogenicity Due to Agonists of Peroxisome Proliferator-Activated Receptors in Senescent Rats: Role of Peroxisome Proliferation, Cell Proliferation, and Apoptosis. (2002) - Youssef, Jihan; Badr, Mostafa
Abstract : Exposure to agonists of peroxisome proliferator-activated receptor alpha (PPAR α ) causes liver cancer in rodents, with aged animals being more susceptible than their younger counterparts to this effect. Treatment with these chemicals produced a five- to sevenfold higher yield of grossly visible hepatic tumors in old rats compared to young animals. The enhanced susceptibility of the aged livers to the carcinogenic effect of PPAR agonists could not be explained by differences in levels of peroxisomal and/or cell proliferation between young and old animals, as neither of these responses was exaggerated with aging. Reported studies have shown that activating PPARa results in the suppression of hepatic apoptosis. This effect is expected to diminish the ability of the liver to purge itself of pre-existing neoplastic cells, allowing them to progress to tumors. New findings from our laboratories show that the aged liver is exceedingly sensitive to the antiapoptotic effect of PPAR agonists. In addition, aged livers showed remarkably higher levels of the antiapoptotic protein Bcl-2 than livers of young, adult, and middle-aged animals. Interestingly, the PPARa agonist Wy-14, 643 significantly diminished elements of the proapoptotic machinery (e.g., Bax, caspases, and fas) in the aged liver, while remarkably increasing elements of this machinery in younger animals. Taken together, while activation of PPARs appears to inhibit apoptosis in livers of senescent animals, activating these receptors seems to stimulate the apoptotic machinery in young animals. This paradoxical effect may be responsible for the exaggerated sensitivity of the aged liver to the carcinogenic effect of agents that activate PPARs.